Vacancy engineering of two-dimensional W2N3 nanosheets for efficient CO2 hydrogenation. Issue 27 (29th June 2022) - Li, Bin; Ma, Bo; Wang, Shu-Yan; Yu, Ming-Ming; Zhang, Ze-Qi; Xiao, Ming-Jun; Zhang, Hong; Wu, Jian-Feng; Peng, Yong; Wang, Qiang; Zhang, Hao-Li
Abstract : N vacancies of two-dimensional W2 N3 nanosheets as confirmed by spherical aberration corrected scanning transmission electron microscopy (Cs-corrected STEM) boosted efficient CO2 hydrogenation. Abstract : Peaking carbon emissions and achieving carbon neutrality have become the consensus goal of the international community to solve the environmental problems threatening mankind caused by accumulative greenhouse gases like CO2 . Herein we proposed vacancy engineering of two-dimensional (2D) topological W2 N3 for efficient CO2 hydrogenation into high value-added chemicals and fuels. Spherical aberration corrected scanning transmission electron microscopy (Cs-corrected STEM) confirmed a large amount of N vacancies on the catalyst surface, which significantly reduced the energy barrier for the formation of the essential intermediates of *CO and *CHO as revealed by density functional theory (DFT) calculations. Consequently, the highly stable catalyst exhibited efficient CO2 hydrogenation superior to many previous reports with a maximum CO2 conversion rate of 24% and a high selectivity of 23% for C2+ hydrocarbons. This work provided not only insight into the vacancy-controlled CO2 hydrogenation mechanism, but also fresh ammunition to bring the remaining potential of 2D topological transition metal nitrides in the field of catalysis.